Effectiveness of a pre-test/post-test model in HPV health education among undergraduate medical students - Xiaohui Yang; Qingjian Ye; Shujun Su; Yuebo Yang; Xiaomao Li (BMC Medical Education)
Abstract Background The HPV vaccination rate of Chinese college students remains low. Therefore, there is an urgent need to provide health education regarding HPV vaccination among college students in China. We used a pre-test/post-test model to implement a health education intervention for the HPV vaccine among undergraduate medical students and subsequently evaluated its effectiveness. Methods A total of 180 undergraduate medical students who were attending classes at the gynaecological department of the Third Affiliated Hospital of Sun Yat-sen University from October 2022 to March 2023 were selected for inclusion in the study. Before class, all students completed a questionnaire and a pre-class quiz to obtain key points in the course. The class regarding HPV and the HPV vaccine was taught by senior teachers. After the course, all students completed a post-class quiz consisting of the same questions as the pre-class quiz. The pre-class and post-class scores were compared to evaluate the effectiveness of this teaching model. Results After the HPV health education intervention in the pre-test/post-test model, the post-class scores were significantly higher than the pre-class scores for different gender, years of study, clinical majors, different willingness of vaccine to receive the vaccine(p < 0.05). Conclusion A pre-test/post-test model may be an effective approach for HPV health education interventions.